Les TIC sont-ils les nouveaux territoires de la diaspora chinoise ? - Joy Raynaud (Netcom)
The increasing use of ICT changes the relationship of men with geographic space. Allowing instant access to endless information, Internet, telephony and television are technologies that produce new perceptions and actions in territories. This study highlights the existence of new interactions between actors (Chinese student community of Montpellier), territories (Chinese and French) and networks (ICTs). ICT are changing the spatial practices by facilitating the installation and organization of the daily life of immigrants in host countries. They also disrupt perceptions by creating a feeling of closeness to their homeland and comfort. Between adaptation to the local and affirmation of a Chinese cultural identity, ICT support the emergence of a dual culture and seem to become the new territories of the Chinese diaspora.